Improvement of recycled aggregate properties through a combined method of mechanical grinding and microbial-induced carbonate precipitation. (1st August 2022) - Gong, Yifan; Chen, Ping; Lin, Yunjie; Wan, Yiling; Zhang, Li; Meng, Tao
Highlights: A combined method of mechanical grinding and MICP is proposed to treat RMAs. The properties of RMAs were improved by using the combined method. Compressive strength of treated RMA-based concrete was significantly enhanced. Abstract: Due to the shortage of natural aggregates, recycled aggregates are gaining great attention in civil engineering. However, recycled aggregates have lower apparent density and higher water absorption and crushing index as compared to natural aggregates. To enhance the properties of recycled mixed aggregates (RMAs), three different treatment routes were adopted in this work: mechanical grinding, microbial-induced carbonate precipitation (MICP), and a combined method of mechanical grinding and MICP. The apparent density, water absorption, and crushing index of RMAs were examined before and after each treatment, and the slump, apparent density, and compressive strength of recycled concretes (RCs) with treated and untreated RMAs were then investigated. In addition, the micro-mechanism of property improvement due to these treatments was analyzed by scanning electron microscopy (SEM). Experimental results revealed that the combined method, in comparison to the other two methods used separately, led to higher apparent density and lower water absorption and crushing index of RMAs. Moreover, RCs treated with the combined method exhibited greater slump, higher apparent density, and superior compressive strength than untreated RCs. Furtherly, compared with commonly used RA treatment methods presented in recent publications, the proposed combined method shows better influence on compressive strength of RCs.